2006
DOI: 10.1039/b511209e
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenicity of pyrethroid insecticidemetabolites

Abstract: There is concern that insecticides are able to mimic the action of 17beta-estradiol by interaction with the human estrogen receptor. Pyrethroids are commonly used insecticides and several have been assessed for potential endocrine disrupting activity by various methods. It has been noted that some metabolites of pyrethroids, in particular, permethrin and cypermethrin, have chemical structures that are more likely to interact with the cellular estrogen receptor than the parent pyrethroid. For this study permeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 24 publications
(31 reference statements)
2
53
0
1
Order By: Relevance
“…A number of epidemiological studies have suggested the relationship between Parkinson's disease (PD) and environmental exposure to pesticides (Tanner and Langston, 1990;Gorell et al, 1998;Priyadarshi et al, 2001); a recent experimental study corroborated the possible underlying mechanism that in vivo exposure to PYRs, deltamethrin and permethrin, increases dopamine transporter and transporter-mediated dopamine uptake in the striatal synaptosome (Elwan et al, 2006). Also revealed by a recent study was the estrogenicity of PYR metabolites (McCarthy et al, 2006). As a consequence of these etiological findings, there has been a growing concern over the association between the long-term exposure to PYRs and as-yet-unknown adverse health effects in human.…”
Section: Introductionmentioning
confidence: 68%
“…A number of epidemiological studies have suggested the relationship between Parkinson's disease (PD) and environmental exposure to pesticides (Tanner and Langston, 1990;Gorell et al, 1998;Priyadarshi et al, 2001); a recent experimental study corroborated the possible underlying mechanism that in vivo exposure to PYRs, deltamethrin and permethrin, increases dopamine transporter and transporter-mediated dopamine uptake in the striatal synaptosome (Elwan et al, 2006). Also revealed by a recent study was the estrogenicity of PYR metabolites (McCarthy et al, 2006). As a consequence of these etiological findings, there has been a growing concern over the association between the long-term exposure to PYRs and as-yet-unknown adverse health effects in human.…”
Section: Introductionmentioning
confidence: 68%
“…Although glyphosate did not induce estrogenic or androgenic effects in the early life stages of stickleback (Gasterosteus aculeatus) at environmentally significant concentrations (Le Mer et al, 2013), its presence at 3.6 mg/L in water was deleterious to female jundia (Rhandia quelen) reproduction, altering steroid profiles and egg viability (Soso et al, 2007). It was also proved that cypermethrin has estrogenic effects (Chen et al, 2002;McCarthy et al, 2006). Several other types of active matter used in the Beninese cotton basin also have harmful effects on the reproduction and growth of fish.…”
mentioning
confidence: 99%
“…56) Moreover, it has been reported that the PYR metabolites, 3-PBAlc and 3-PBAld, possess estrogenic activity of approximately 10 5 less than that of 17b -estradiol. 57,58) These experimental data, although the tested dose was not necessarily low, could provide a new explanation for some of the findings observed in human studies.…”
Section: Results Unitsmentioning
confidence: 89%